« Cent dromadaires et quelques arrangements » Notes sur la diya (prix du sang) et son application actuelle au Soudan et en Algérie - Yazid Ben Hounet (Revue des Mondes Musulmans et de la Méditerranée)
This paper deals with the fundaments and reasons of diya’s (blood money) and its actual application in two distinctive geographical areas: Sudan and Algeria. We will shed light on the invariants and specificities of its actual use and propose /offer some perspectives on cultures and practices of reconciliation in these two countries. This article aims at reporting the actual outlines of diya depending on the fact of whether it is inscribed (Sudan) or not (Algeria) in penal state law. We will focus on some local conceptions of crime and reconciliation, the role of Islamic law and custom (‘ûrf), pragmatic arrangements according to the studied contexts, particularly on the monetary amount’s evaluation of diya, the kind of homicide that could be compensated and the responsibilities in compensation’s matter.